Tolerability and Efficacy of Rivaroxaban Versus Warfarin for Non Vulvular Atrial Fibrillation - Mahboob Ur Rehman, Asma Rauf, Amjad Ali Shah, Anwar Ali, Amjad Ibrar, Ali Raza (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Atrial fibrillation (AF) is the most widespread chronic heart arrhythmia, affecting 1–2 % of the general population. Objectives: Patients with non-valvular atrioventricular fibrillation are the major focus of this research. Rivaroxaban is compared against warfarin in terms of tolerability and efficacy. Material and methods: This cross sectional comparative study was conducted in Pakistan Institute of Medical Sciences Islamabad during January 2020 till December 2020. A total of 120 OPD patients who satisfied the study’s inclusion and exclusion criteria were included in the research after it was given the green light by the hospital’s ethics committee. A complete medical history and physical examination were required to ensure that all participants met the criteria for inclusion. It was determined that obtaining express written consent was essential. Results: As indicated above, 15 individuals were removed from the study; six patients in the NOAC group refused to participate and departed the study; while four patients were lost to follow-up. In this study, rivaroxaban was administered to twenty-one participants, whereas warfarin was administered to the remaining twenty-four. Conclusion: Oral anticoagulants for stroke prevention in non-valvular AF have advanced in development, benefiting patients and clinicians alike with fewer medication and food interactions, no monitoring need, and a wider therapeutic index.